1999
DOI: 10.1029/98jb02734
|View full text |Cite
|
Sign up to set email alerts
|

Gas bubble dynamics model for shallow volcanic tremor at Stromboli

Abstract: Abstract. Volcanic tremor at Stromboli (Aeolian islands, Italy) is correlated to small infrasonic transients [Ripepe et al., 1996] which repeat almost rythmically intime in a range between 0.8 and 1.2 s. We demonstrate that infrasonic transients are associated to small gas bubble (-•0.5 m) burstings which produces no transients in the seismic signal. Tremor ground displacement attenuates with the inverse of the distance from the craters indicating that the source is shallow. Short-term energy release shows tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
89
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(93 citation statements)
references
References 49 publications
4
89
0
Order By: Relevance
“…The role of puffing in the degassing dynamics at Stromboli has been previously investigated only by indirect analysis of thermal image and infrasonic data (Ripepe and Gordeev, 1999). Here we provide the first direct gas measurement based constraints on the total SO 2 mass and flux rate from puffing.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The role of puffing in the degassing dynamics at Stromboli has been previously investigated only by indirect analysis of thermal image and infrasonic data (Ripepe and Gordeev, 1999). Here we provide the first direct gas measurement based constraints on the total SO 2 mass and flux rate from puffing.…”
Section: Discussionmentioning
confidence: 92%
“…Gas puffing activity at Stromboli has been characterised over the last two decades by combined analysis of infrasonic transients and thermal imagery (Ripepe and Gordeev, 1999;Harris and Ripepe, 2007). Based on outcomes of geophysical model calculations predicated upon results of the above acoustic and thermal studies, it was concluded that puffing activity may account for a substantial fraction ( $ 45%) of Stromboli's total gas flux Ripepe et al, 2008).…”
Section: Insights Into Gas Puffingmentioning
confidence: 99%
“…In particular, energy bursts commonly observed in the infrasonic range (few hertz to tens of hertz ), both in acoustic and seismic measurements, were associated with bubble dynamics (resonance or breaking) inside the volcano reservoir (e.g. Ripepe and Gordeev, 1999;Vergniolle and Brandeis, 1994;Vergniolle et al, 1996;Vergniolle and Caplan-Aurebach, 2004;.…”
Section: Albarello Et Al: Monitoring Methane Emission Of Mud Volcmentioning
confidence: 99%
“…Assuming the resonant model, frequency content of tremor may depend on the interactions between viscous attenuation of magma and elastic properties of ground [Chouet, 1985]. However, tremor spectral content may be also modeled as the viscoelastic reaction of the magma-gas medium to pressure changes in magma induced by gas expansion [Ripepe and Gordeev, 1999].…”
Section: Introductionmentioning
confidence: 99%